Combination of αCD4 antibody and retinal antigen injection induces long-term disease control in autoimmune uveitis - Qiao, Dijie; Zhang, Lu; Zhong, Yajie; Liu, Dongmei; Chen, Zilin; Chong, Wai Po; Chen, Jun (Frontiers in Immunology, 2025)
IntroductionAutoimmune uveitis is a sight-threatening inflammatory eye disease driven by immune dysregulation. We previously introduced a therapeutic strategy involving the in vivo induction of retinal-antigen-specific regulatory T cells (Tregs) via αCD4 antibody injection followed by administration of the retinal self-peptide IRBP1-20, which effectively suppresses inflammation during the onset of experimental autoimmune uveitis (EAU).MethodsWe evaluated the long-term therapeutic efficacy of this approach in a chronic EAU model. EAU was induced in C57BL/6 mice, and treatment was administered at each onset or relapse episode over a 28-week period. Disease progression was monitored by clinical scoring and funduscopy, with further assessment using histopathology and optical coherence tomography (OCT). Flow cytometry was employed to analyze immune cell infiltration, and RNA sequencing of ocular tissue was performed to assess gene expression changes.ResultsMice receiving aCD4 antibody and IRBP1-20 showed sustained disease control up to 28 weeks, with reduced ocular inflammation, less retinal damage on OCT, and decreased immune cell infiltration compared to untreated controls. Transcriptomic analysis revealed significant downregulation of inflammation-related genes following treatment.ConclusionThese findings support the long-term immunomodulatory effect of combining αCD4 antibody and retinal antigen injection, offering a potential strategy for managing chronic progressive autoimmune uveitis.